BUILDING BRAND IMAGE IN THE REFILL PERFUME INDUSTRY THROUGH CUSTOMER EXPERIENCE CREATION AND WORD OF MOUTH - Sujono, Hernandi; Hurriyati, Ratih; Wibowo, Lili; Hendrayati, Heny (Faculty of Economic and Business, University of Pasundan, 2025)
The rise in perfume usage has led to many brands or companies establishing refill perfume businesses. The refill perfume industry currently faces challenges in building a strong brand image. This research aims to examine the influence of customer experience and word of mouth in establishing the brand image of the refill perfume industry. The method used in this study is a quantitative descriptive approach with Structural Equation Modeling-Partial Least Square (SEM-PLS). The analysis tool used is SmartPLS. The population for this study consists of refill perfume consumers from each branch of refill perfume stores in five major cities in West Java Province: Bandung, Tasikmalaya, Garut, Bekasi, and Cirebon. The minimum sample size taken is 332 respondents, using cluster sampling. The results of this study indicate the influence and significance of customer experience and word of mouth in building the brand image of the refill perfume industry.